DIAGNOSIS SKIZOFRENIA PADA TOKOH UTAMA NOVEL HAGURUMA KARYA AKUTAGAWA RYUUNOSUKE: TINJAUAN PSIKOANALISIS SIGMUND FREUD - Wanda Hanifah (Faculty of Cultures and Languages UIN Raden Mas Said, 2022)
This study aimed to discuss the main character in a fictional novel called Haguruma by Akutagawa Ryuunosuke. The purpose of this research was to analyze the mental disorder of the main character in the novel by using Sigmund Freud's psychoanalytic approach comprising the id, ego, and superego. This was descriptive-qualitative research in which data were collected through a documentation technique. The object of the study was Haguruma, with the the main character’s psychology as the formal object of the current study. The primary data were taken from Haguruma, while all sources related to the novel became the secondary data. The results showed that the main character suffered from schizophrenia described as someone experiencing trauma, high anxiety, drug addiction, insomnia, delusions and depression.